Evaluation of thermal barrier coatings and surface roughness in a single-cylinder light-duty diesel engine. (March 2021) - Somhorst, Joop; Oevermann, Michael; Bovo, Mirko; Denbratt, Ingemar
The effect of two thermal barrier coatings and their surface roughness on heat transfer, combustion, and emissions has been investigated in a single-cylinder light-duty diesel engine. The evaluated thermal barrier coating materials were plasma-sprayed yttria-stabilized zirconia and hard anodized aluminum, which were applied on the piston top surface. The main tool for the investigation was cylinder pressure analysis of the high-pressure cycle, from which the apparent rate of heat release, indicated efficiency, and heat losses were derived. For verification of the calculated wall heat transfer, the heat flow to the piston cooling oil was measured as well. Application of thermal barrier coatings can influence engine operating conditions like charge temperature and ignition delay. Therefore, extra attention was paid to choosing stable and repeatable engine operating points. The experimental data were modeled using multiple linear regression to isolate the effects of the coatings and of the surface roughness. The results from this study show that high surface roughness leads to increased wall heat losses and a delayed combustion. However, these effects are less pronounced at lower engine loads and in the presence of soot deposits. Both thermal barrier coatings show a reduction of cycle-averaged wall heat losses, but no improvement in indicated efficiency. The surface roughness and thermal barrier coatings had a significant impact on the hydrocarbon emissions, especially for low-load engine operation, while their effect on the other exhaust emissions was relatively small.